PEMANFAATAN MANAJEMEN PEMBELAJARAN AUGMENTED REALITY DALAM MENDUKUNG PROGRAM MERDEKA BELAJAR KAMPUS MERDEKA (MBKM) - Kasim, M. Habibi; Imtiyaz, Muhammad Farisal; Nur, Siti; Rohman, Aa Abdul; Abdul Rohim, Adi (PENDIDIKAN SAINS DAN TEKNOLOGI, 2024)
The boredom in the teaching and learning process is very much felt, especially in the new normal era. This is felt by both lecturers and students. So that an effective and interesting learning media is needed in its delivery, of course the lecturers think hard about the right solution so that the material is conveyed and students can understand it. Augmented Reality (AR) is one of the interactive media in learning, its appearance in the form of 3D objects, as well as sound and image improvisation that supports it, is expected to be interesting and fun in learning, especially at Nusantara Islamic University. It is hoped that this method can answer "saturation in learning" because it can attract the focus and attention of students. In order to prepare students to face social, cultural, world of work changes and rapid technological advances, student competencies must be prepared for the needs of the times. Link and match not only with the world of industry and the world of work but also with the rapidly changing future. Higher Education is required to be able to design and implement innovative learning processes so that students can achieve learning outcomes covering aspects of attitude, knowledge, and skills optimally and always relevant. The Freedom to Learn Policy - Merdeka Campus is expected to create a better quality of human resources.